Moodle-based arabic sentence writing materials: A Hannafin & Peck development study - Anjani Prameswari Safiratuljannah; Imam Asrori; Mohammad Ahsanuddin (Jurnal Penelitian Ilmu Pendidikan, 2025)
This study aims to develop Arabic sentence-writing learning materials (kitabah al-jumal) based on the Moodle Learning Management System for beginner-level students, particularly graduates of non-Islamic senior high schools who have limited foundational competence in Arabic. This research employed a Research and Development (R&D) design using the Hannafin and Peck model, which consists of analysis, design, and development and implementation stages, with the study limited to the product validation phase. The analysis stage involved observations, interviews with lecturers, and diagnostic tests to identify learners’ needs. The design stage produced five core instructional units, PDF modules, learning videos, and their integration into Moodle. The development and implementation stage comprised product construction and expert validation, while product feasibility was assessed using questionnaires and analyzed using percentage calculations. The material expert provided a score of 77% (good/feasible) with several revision notes related to linguistic accuracy, whereas media expert validation scored 90.67% (very feasible) with no required revisions. Limited implementation with 32 students indicated that the product was easy to use and supported comprehension of basic sentence structures, suggesting that the developed materials are feasible and appropriate for beginner learners and may serve as a foundation for further Moodle-based Arabic instruction in higher education.